The Building Islamic Humanism in The Context of Peoples Benefit - Badrudin, Badrudin (Universitas Malikussaleh, 2020)
The purpose of this study is a means to realize the importance of humanitarian education in building Islamic humanism and understanding the urgency of its values. Islamic law basically contains the values of universal humanism. This is apparent in syari’a that was born as a mercy to the universe. Islamic Humanism departs from empirical social reality and human condition. Religion is interpreted in a contextual manner, resulting in a process of dialogue between text and reality, between normativity and historicity. That way space can be open to the fulfillment of humanity. In general, humanism means the dignity and worth of every human being, and all efforts to enhance his natural abilities ( physical non-physical) in full. And humanism can be simply understood as an effort to affirm the humanity of man.